Global Householding, Gender, and Filipino Migration: A Preliminary Review - Porio, Emma E (Archīum Ateneo, 2007)
Utilizing data from the National Statistics Office's Family Income and Expenditure Survey (NSO-FIES) and three case studies, this article argues that overseas labor migration inserts households into a globalized life that reconfigures patterns of "household making" through remittances and income mobilization activities. In turn, these income/remittance patterns and the mobilization of reproductive labor have changed the ways households left behind in the Philippines organize child care/elderly care, household maintenance, and resource mobilization within and across households. The article concludes with insights gained in utilizing the household as a unit of analysis in examining the interfaces and interconnections between global-local processes and Filipino migration.